Complex Interaction Analysis: Labor Force Participation, Education, Unemployment, Health, and Poverty on Economic Growth in Nusa Tenggara Barat - Linda Purwati; Mansur Afifi; Siti Sriningsih (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This study aims to analyze the effect of labor force participation rate, education level, open unemployment rate, health level, and poverty level related to economic growth in West Nusa Tenggara province. The type of research used is quantitative research with a descriptive approach. The data used is secondary data taken from the Central Statistics Agency (BPS) of Nusa Tenggara Barat Province. With data collection techniques documentation. The data analysis method in this study uses panel data regression using the eviews 10 analysis tool. Panel data in this study is a combination of cross section data (data from 10 districts / cities in West Nusa Tenggara province) and time series data (data from 2011-2022). The results of the analysis show that the variable labor force participation rate, education level, open unemployment rate, and health level have a positive or significant effect on economic growth in the province of West Nusa Tenggara while the poverty rate variable has a negative or insignificant effect on economic growth in the province of West Nusa Tenggara. From the results of the determinant test (R2) shows an R-squared value of 0.492871. This means that the independent variables are able to explain the variation of the dependent variable, namely the labor force participation rate, education level, open unemployment rate, health level, and poverty rate on economic growth in the province of West Nusa Tenggara by 49.28 percent.